Is it time to revisit contraindications to organ donation from donors with a JAK‐2 mutation? Safe use of a liver allograft from a donor with essential thrombocythaemia. (27th March 2015) - Haldar, Debashis; Chen, Frederick; Byron, Jane; Elsharkawy, Ahmed Mohamed; Perera, M Thamara PR
Summary Transplantation can cure end‐stage liver disease and hepatocellular carcinoma. However, the balance of organ demand and provision is heavily tipped to the detriment of patients. Patients awaiting transplantation rely on the greater use of marginal donors that may carry a risk to the recipient. UK authorities have decreed donor haematological malignancy an absolute contraindication. The authors describe the first report of a patient being safely transplanted with a liver from a donor who suffered from JAK2 V617F mutation‐driven essential thrombocythaemia to a patient with a critical burden of hepatocellular carcinoma. A year after transplantation, the patient has neither evidence of acquisition of the donor's pathology, nor evidence of carcinoma recurrence. The case highlights the responsibility of the recipient team to maximize the use of organs by expert risk assessment. Dissemination of experience should inform future decisions, benefit patients and bolster utility in an era of growing waiting‐list mortality.